2010
DOI: 10.1109/tpwrs.2009.2030421
|View full text |Cite
|
Sign up to set email alerts
|

A Variable Speed Wind Turbine Control Strategy to Meet Wind Farm Grid Code Requirements

Abstract: This paper presents a new operational strategy for a small scale wind farm which is composed of both fixed and variable speed wind turbine generator systems (WTGS). Fixed speed wind generators suffer greatly from meeting the requirements of new wind farm grid code, because they are largely dependent on reactive power. Integration of flexible ac transmission systems (FACTS) devices is a solution to overcome that problem, though it definitely increases the overall cost. Therefore, in this paper, we focuses on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
162
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(171 citation statements)
references
References 27 publications
0
162
0
5
Order By: Relevance
“…The relation is: VDC > 1.633 Vg-LL, as stated in [34]. In order to realize a transfer of active power generated by the PMSG to the grid, the capacitor voltage is varied during wind turbine operations [35]. The dynamic model of the grid connection, in the reference frame rotating synchronously with the grid voltage, is given as follows [29]:…”
Section: The Grid Side Voltage Source Converter-controllermentioning
confidence: 99%
See 1 more Smart Citation
“…The relation is: VDC > 1.633 Vg-LL, as stated in [34]. In order to realize a transfer of active power generated by the PMSG to the grid, the capacitor voltage is varied during wind turbine operations [35]. The dynamic model of the grid connection, in the reference frame rotating synchronously with the grid voltage, is given as follows [29]:…”
Section: The Grid Side Voltage Source Converter-controllermentioning
confidence: 99%
“…Also in order to transfer all the active power generated by the wind turbine the dc-link voltage must remain constant [35], as per in the following constraint [36]:…”
Section: The Grid Side Voltage Source Converter-controllermentioning
confidence: 99%
“…However, when a short circuit fault occurs in the power system, the electromagnetic torque of the machine reduces proportional to the square of the remnant voltages causing the rotor to accelerate beyond its safety limits. Also, as the fault occurs, the induction machine absorbs large reactive power in order to recover the air gap flux [9]. Otherwise, large difference between electromagnetic and mechanical torques can lead to the instability of the machine.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated in [6,17] that direct drive wind turbine can improve transient and voltage stability of its adjacent grid. In [9], it is also shown that the capability of fixed speed wind generators to ride through the fault can be improved by installing direct drive wind turbine in parallel and series. The control strategies are designed considering the grid codes set by the Federal Energy Regulatory Commission (FERC) but the effect of overloading the converter current is not shown.…”
Section: Introductionmentioning
confidence: 99%
“…En las turbinas de velocidad variable, la velocidad de giro se controla mediante un convertidor electrónico de potencia (Muyeen et al, 2010). Éste tiene una doble misión, además de controlar la velocidad, se encarga de convertir la tensión alterna producida por el generador en corriente continua.…”
Section: Introductionunclassified